ГадаадЫн ХөРөнГө ОРУУЛаЛТЫн ТаЛааР ТөРөөС БаРИМТЛаХ УЛС ТөРИйн БОдЛОГО БОЛОвСРУУЛаХ нөХцөЛ БайдаЛ - С.БАЗАРПҮРЭВ; Б.НАНДИН-ЭРДЭНЭ (Politology, 2023)
Mongolia is rich in natural resources, including metals and minerals, gas and oil with less economic resources and lack of workforce. Thus Mongolia need to attention on making policy of foriegn investment.Despite government efforts to attract foreign investments through investment policies and incentives, but several challenges still need beaddressed.Furthermore, government should be focus on stable political policy.Foreign investment on the political policy of this study when looking at the frame of Institute for Government and Law will be discussed in terms of the law and regulation.